Electrocardiographic alteration among first degree relatives with serologic evidence of Trypanosoma cruzi infection: a sibship study - C. Morini, Julio; Berra, Héctor; O. Dávila, Héctor; F. Pividori, Juan; A. Botasso, Oscar (Memórias do Instituto Oswaldo Cruz, 1994)
To analyze whether electrocardiographic alterations (ECGA) in patients with antibodies to Trypanosoma cruzi showed a pattern of familial aggregation, a sample of 379 young adults (166 men and 213 women) distributed in sibships, were assessed for the presence of anti-T. cruzi antibodies, and subjected to a complete clinical examination and a standard resting electrocardiogram (ECG). Positive T. cruzi serology was detected in 165 individuals, 48 of them showing an abnormal ECG (overall prevalence 29%). One hundred and eleven seropositive individuals were distributed in 45 sibships, each of them constituted by more than one seropositive sib, with ECGA being present in 34 out of these patients. Seropositive subjects with ECGA were detected in 27 sibships. Since the index case within each sibship is counted exactly once, affected individuals selected at random as propositi were extracted to calculate the prevalence of ECGA among first degree relatives of probands. Abnormal ECGs were recorded in 7 out of 45 sibs yielding a prevalence that did not differ from estimations registered in the general population or seropositive sibs. Data from the present sample show no familial aggregation for the occurrence of ECGA in patients with T. cruzi. infection.